The Influence of Education with KIA Books on the Completeness of Infant Immunizations - Mutmaina Harun; Anik Sri Purwanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Immunization is one of the most effective public health interventions to reduce infant morbidity and mortality from preventable diseases. However, incomplete infant immunization coverage remains a significant problem, particularly in areas with limited maternal knowledge and access to health information. The Maternal and Child Health (KIA) book serves as an educational tool designed to improve mothers’ understanding of child health services, including immunization schedules. Education using the KIA book is expected to enhance maternal awareness and support the completeness of infant immunizations.Objective: This study aimed to determine the influence of education using the KIA book on the completeness of infant immunizations. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. Data on the completeness of infant immunizations were collected before and after the educational intervention using immunization records. The data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05.Results: The results showed a significant improvement in the completeness of infant immunizations after education using the KIA book. Statistical analysis revealed a Wilcoxon signed-rank test value of p = 0.000, indicating a significant influence of KIA book-based education on immunization completeness.Conclusion: Education using the KIA book has a significant positive influence on the completeness of infant immunizations. The KIA book is an effective educational medium to improve maternal knowledge and compliance with infant immunization schedules. Integrating KIA book-based education into routine maternal and child health services is recommended to enhance immunization coverage.